Winding Arrangement of A New Type Hollow Rotor BLDC Motor - Farina Sulaiman; R.N. Firdaus; M. S. Ahmad; A. Jidin; T. Sutikno (Institute of Advanced Engineering and Science, 2018)
This paper discusses about winding arrangement of fractional slot of a new type hollow rotor Brushless Direct Current (BLDC) motor. Hollow rotor has higher performance compared to other BLDC motor because it minimizes the unused flux below permanent magnet and maximize torque produce by the motor. It’s also known that 8 pole motor is favorite used in industrial because it has an optimum space of permanent magnet for a smaller motor size. The number of pole will affect the maximum speed of the rotor. Thus, the objective of this research is to investigate the best winding arrangement for 8 pole of hollow rotor that could produce the highest electromagnetic performance. At starts, four combinations of slot number and coil sizes had been selected. Structural comparison in term of coil vector and winding arrangement is studied. Finite Element Method (FEM) had been used to simulate the parameters such as backemf and torque waveforms. It was convinced that 9 slot 8 pole with 0.6 size of coil produces the best performance. The confirmed model had been fabricated and measured. Both results from FEM and measurement are compared in term of backemf and torque where percentage differences are 7.4 % and 8 %, respectively. As conclusion, this research shows the fundamental of winding arrangement of fractional slot of motor especially 8 pole motor.